Analisis Kinerja Keuangan Pemerintah Daerah Berdasarkan Value For Money Pada Pemerintah Kota Surabaya Tahun 2015-2021 - Joanico Francisco Ximenes Alexandre; Muhammad Taufik; Hidayat Hidayat (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study was to analyze the Financial Performance of Local Governments based on Value for Money at the Surabaya City Government in 2015-2021, namely in terms of economy, efficiency and effectiveness. The method of analysis in this research is Descriptive Qualitative Analysis Method. The data collection technique used is the report on the realization of the regional budget for revenues and expenditures (APBD) of the Surabaya City Government in 2015-2022. The data was obtained from the Surabaya City Regional Revenue and Financial Management Office through the Surabaya City Regional Government website. Measurement of economic value is based on the comparison of the budget with the realization of the budget. The measurement of efficiency value is based on the comparison of output with input, where the output is obtained from the performance achievement of the Surabaya City Government. While the input of economic value that has been obtained and for measuring the value of effectiveness is based on the comparison of outcomes with outputs, where the outcome is the target to be achieved, while the output is the performance achievement of the Surabaya City Government. The results of this study indicate that the financial performance of the Surabaya City Government shows that the performance of the Surabaya City Government is quite economical in 2015-2021. The economic level is quite stable in a span of seven years and has an average achievement of 87.74%. In terms of efficiency, it shows that the financial performance of the Surabaya City Government from 2015 to 2021 on average for seven years is included in the efficient criteria. In terms of effectiveness, the Surabaya City Government's financial performance for the 2015-2021 fiscal year shows an unstable condition, so that from the level of effectiveness, the Surabaya City Government must try to improve it again.